The Big Con: How the Consulting Industry Weakens our Businesses, Infantilizes our Governments and Warps our Economies - Mazzucato, Mariana; Collington, Rosie (Allen Lane, 2023)
There is an entrenched relationship between the consulting industry and the way business and government are managed today which must change.Mariana Mazzucato and Rosie Collington show that our economies' reliance on companies such as McKinsey, Boston Consulting Group, Bain & Company, PwC, Deloitte, KPMG and EY stunts innovation, obfuscates corporate and political accountability and impedes our collective mission of halting climate breakdown.The 'Big Con' describes the confidence trick the consulting industry performs in contracts with hollowed-out and risk-averse governments and shareholder value-maximizing firms. It grew from the 1980s and 1990s in the wake of reforms by both the neoliberal right and Third Way progressives, and it thrives on the ills of modern capitalism, from financialization and privatization to the climate crisis. It is possible because of the unique power that big consultancies wield through extensive contracts and networks - as advisors, legitimators and outsourcers - and the illusion that they are objective sources of expertise and capacity. To make matters worse, our best and brightest graduates are often redirected away from public service into consulting. In all these ways, the Big Con weakens our businesses, infantilizes our governments and warps our economies.Mazzucato and Collington expertly debunk the myth that consultancies always add value to the economy. With a wealth of original research, they argue brilliantly for investment and collective intelligence within all organizations and communities, and for a new system in which public and private sectors work innovatively for the common good. We must recalibrate the role of consultants and rebuild economies and governments that are fit for purpose.

States of Change - Learning programme - Nesta (Nesta, 2018)

What have we learned about learning? Unpacking the relationship between knowledge and organisational change in development agencies - Yanguas, Pablo (DIE - Deutsches Institut für Entwicklungspolitik, 2021)
Development cooperation has spent decades wrangling over the merits, evidence, and implications of what we may term “the learning hypothesis”: the idea that increased knowledge by development organisations must logically lead to increased effectiveness in the performance of their development activities. Organisations of all stripes have built research and monitoring and evaluation (M&E) departments, adopted a multitude of knowledge management systems and tools, and tinkered with different ways to structure their organograms to stimulate knowledge sharing and learning. The topic of organisational learning is particularly significant as the global development community grapples with increasingly complex problems and the aspiration of evidence-based policymaking. This paper presents an analytical framework for interrogating “the learning hypothesis”, breaking it down into causal steps: knowledge causes learning, learning causes organisational change, change causes effectiveness. The framework focuses on the first two sub-hypotheses, mapping out the conceptual space around them by outlining potential relationships between different types of knowledge – tacit and explicit, internal and external – and between different types of learning – operational and strategic. This map provides a foundation for three key research questions: What impact has the rising knowledge agenda had on development organisations? Which factors appear to enable or inhibit organisational learning? What is the relationship between operational and strategic learning and organisational change? A review of available evaluations and studies, including two cases from former UK Department for International Development (DFID) and the World Bank, reveals that there is insufficient evidence to support the causal claim that knowledge leads to learning and thereby to organisational change in development agencies. Sources point to tacit learning prevailing while explicit knowledge management systems flounder, and external advocacy agendas appear more compelling than internal research and evaluation products. It is not entirely clear how, or indeed, whether operational and strategic learning intersect, with delivery-level lessons hardly aggregating into structural or policy shifts. Organisational change – even that aimed at enhancing learning – is rarely based on lessons learned from practice. More research is necessary to fully unpack the learning hypothesis, but what limited evidence is available disproves rather than confirms its central claim. This has significant implications for the future of learning in development agencies as advocated by thought leaders, researchers, and reformers. In particular, the latter should consider an evidence-based reassessment of the function and value-for-money of research and M&E in development practice, and a more critical examination of the politics of external advocacy efforts around innovative aid approaches like thinking and working politically, adaptive management, or results-based management.
Publisher: German Development Institute / Deutsches Institut für Entwicklungspolitik (DIE) Version Number: 1.0